Sociocultural and Linguistic Diversity in the Mid-European (Slovak) Economic and Technological Space - Burcl, Pavol; Kozarova, Zuzana; Csalova, Olga; Pavlova, Renata; Zelenicka, Elena (Integrat͡s︡ii͡a︡ obrazovanii͡a︡ = Integration of education, 2020)
Introduction. Social cultural aspect and linguistic diversity of educational background play an important role in teaching a foreign language. Although there are a lot of publications on this theme, it is hardly possible to find surveys which study the impact of globalization accompanied by the English language expansion, on transformation of cultural identity. The aim of this article is to analyse changes of social cultural phenomena and linguistic diversity in common life and foreign languages education in a Mid-European (mostly Slovak) economic and technological spheres. Materials and Methods. Within this research the content analysis method was employed together with critical comparison of relative scientific papers and other materials in the respect of the problem investigated. Questionnaires were developed and educators who run practice oriented professional programmes were interviewed. After the results of the interview being analysed and synthetized, some crucial points of the discussed problem were revealed. Results. The research revealed the main factors which determine diversity of linguistic communication in a Mid-European former socialist country (Slovakia as an example); reasons and types of social cultural transformations in the society under research were analysed; economic and technological conditions of the transformations discussed were defined; recommendations for educators who run practice oriented professional programmes were developed. Discussion and Conclusion. The results of the research done are considered to be some contribution to the development of bilingual practice oriented education under the condition of European economic and technological integration. However, the task of reserving peculiar cultural values of the nation which is subject to unavoidable social cultural transformations is the major one in this respect.